Promouvoir des programmes d'éducation à la sexualité positive, inclusive et émancipatrice: méta-analyse qualitative intersectionnelle des besoins exprimés par les jeunes - Descheneaux, Julie; Fédération du Québec pour le Planning des naissances; Pagé, Geneviève; Piazzesi, Chiara; Pirotte, Magaly (Service aux collectivités de l'UQAM/Fédération du Québec pour le Planning des naissances, 2018)
Keywords: 2000 à aujourd'hui; 2010-2019; SAC; approches et analyses; discipline; intersectionnalité; pratiques féministes; pédagogie; périodes historiques; recherche en milieux de pratique; recherche partenariale; ressource en ligne; santé; santé sexuelle; thématiques; éducation

"Everyone needs a class like this": High school students' perspectives on a gay and lesbian literature course - Helmer, Kirsten (Educational Forum, 2015)
This article offers insights on how students experienced and made sense of their learning in a trimester-long high school Gay and Lesbian Literature course. Drawing on questionnaires and interviews that the students completed as part of a larger ethnographic study of this class, the author shows how a queer-themed literature curriculum is relevant for both LGBTQ-identifying and straight-identifying students and contributes to a better school climate.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; discipline; identités LGBTQIA2+; pédagogie; périodes historiques; ressource en ligne; régions géographiques; science de l'éducation; thématiques; école secondaire; états-unis